DOSIS PUPUK PHOSPHAT DAN TAKARAN PUPUK KANDANG SAPI PADA PERTUMBUHAN DAN HASIL TANAMAN WIJEN (Sesamum indicum L) - Baidowi, Mohamad; Wibowo, Agung Setya (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
Objective of the study was to know the effect of application of phosphate fertilizer and cow manure on the growth and yield of sesame. The experiment was conducted from February to May 2017 at field Rembang Village, Kesamben district, Blitar Regency. This research is factorial randomized block design consisting two factor with three replication following the treatments of phosphate fertilizer P1= 100 kg ha-1, P2= 150 kg ha-1, P3= 200 kg ha-1 and cow manure dose O1 = 5 ton ha-1, O2= 7,5 ton ha, S3= 10 ton ha-1 were test. The results showed that there ’s no interaction between dose of phosphate fertilizer treatments and dose of cow manure treatments. The dose 100 kg ha-1 of phosphate fertilizer is the best treatment on growth and yield of sesame. The dose 10 ton ha of cow manure is best treatment on growth and yield of sesame.